TAMAN ANGGREK DI BANJARBARU - Zhafirah, Haya; Andini, Dila Nadya (UNIVERSITAS LAMBUNG MANGKURAT, 2023)
Orchids are one of the most popular plants among the public because most of the orchids grow in tropical countries like Indonesia. In Indonesia, there are around 5,000 species of orchids spread across several provinces and 38 percent of them are in Kalimantan. There are several types of natural orchids that are becoming rare due to the rampant exploitation of these flowers, so that several types of orchids are starting to become endangered. Therefore, the conservation of orchid plants has recently begun to be increased, the government of South Kalimantan is one of those who are intensively conserving orchids with the aim that existing orchid species do not become extinct. However, the challenge is how to get the whole community involved in this conservation, not just a group of related people. On the other hand, orchids have a special attraction in the eyes of the public, with their attractiveness, the Orchid Recreation Park has the potential to be used as a recreation area that provides open education to all people so that they can help preserve the orchids themselves. The concept of metaphorical architecture was also chosen as the design concept for this Recreation Park with the design principle that it is hoped that the design of this Recreation Park will attract more visitors.